A Historical and Analytical Description of the South Florida Recreational Tournament Fishery for Broadbill Swordfish, Xiphias gladius - Brewer, Elaine J. (NSUWorks, 2011)
Swordfish (Xiphias gladius) are increasingly sought after by recreational anglers around the world. The Florida Straits in particular are an important breeding and nursery area for North Atlantic swordfish, as well as for being historical fishing grounds for both recreational and commercial swordfish fisheries. The recreational fishery for swordfish in southeastern Florida is categorized into two historical periods. The first period started in 1977 and consists of the first tournaments in the area to specifically target swordfish. Despite high initial catches, low catch numbers forced the tournament fishery to close in 1983. During the second period of the fishery (starting in 2000 to today) the tournament fishery for swordfish has reemerged. Data from a total of 98 swordfish tournaments (17 historic, 81 current) have been collected. For comparison, information has been gathered from 72 istiophorid billfish tournaments within the modern (second) period. These data were gathered from tournament directors, websites, and personal communication with participants of the tournaments. The tournaments studied took place on the east coast of Florida from Stuart south to Key West, with a majority being held between Lighthouse Point and Islamorada in the Florida Keys. Although participation correlates to the number of catches, catch per hour (CPH) remains on a slow although not significant decrease over time. The entry fees for these modern period swordfish tournaments range from $200-600, while those for the more exclusive billfish tournaments are tenfold swordfish entry costs. Similarly, awarded prize monies of billfish tournaments are tenfold and significantly larger than prize monies for swordfish tournaments. The average weight of landed swordfish has shifted slightly in both the historic and the modern periods. Despite the oscillation of catch numbers throughout the two time periods, the weight of caught swordfish remained roughly the same. This may be from the minimum length restrictions implemented in the modern time period, a regulation which did not exist during the tournaments of the historic period.